Analisis Transparansi, Optimalisasi Pengelolaan Zakat dan Efisiensi Terhadap Lembaga Zakat Infaq dan Shodaqoh Muhammadiyah (LAZISMU) Kabupaten Ponorogo - Erma Novitasari; Titi Rapini; Riawan Riawan (ASSET: Jurnal Manajemen dan Bisnis, 2020)
Many zakat institutions are competing to get a lot of funds but still do not pay attention to what they should pay attention to in accordance with the Shari’a and applicable rules. The existence of this research is to see the extent of transparency, optimization and efficiency level of zakat funds at the amil Zakat, Infaq and Shodaqoh Muhammadiyah Ponorogo institutions which have been available since 2005. The date used are primary and secondary date obtained from LAZISMU Ponorogo with interview techniques. The results of the discussion of this thesis is that the transparency variable is said to be transparency buy there are some shortcomings. The optimization variable can be said to be optimal although there is also something that needs to be added as an amplifier and the efisiency variable is very efficient with a value in 2017 of 17,19% and in 2018  of 18,15% an increase in the level of efisiency is due to the addition of employees.